Analysis of Cash Inflow and Outflow Recording at Satset Coffee Shop in Minasa Upa - Wahyuni; Sri Ulfa Ulandari; Aulia Zahra; Lidia Arianti Agustin; Muh.Rafi Khalik; Muh.Alfit Maulana; A.Yusuf Muhammad (Masterpiece, 2026)
Micro, Small, and Medium Enterprises (MSMEs) contribute substantially to Indonesia’s economic development, yet inadequate financial recording remains a major obstacle to effective business management and sustainability. This community engagement activity aimed to analyze the cash inflow and cash outflow recording practices of Satset Coffee Shop in Minasa Upa, Makassar, and strengthen the partner’s capacity to implement a simple and systematic accounting system. The activity employed a participatory approach involving preliminary observation, problem identification, interviews, financial education, practical training, transaction simulation, mentoring, and evaluation. Data were obtained through direct observation, interviews with the owner and employees, transaction documentation, and examination of cash records. The initial assessment revealed several weaknesses, including the absence of a structured cash book, inadequate documentation of supporting transactions, the mixing of personal and business finances, and limited internal control over cash management. Following the intervention, the partner successfully implemented a cash inflow and outflow recording format, separated personal and business transactions, organized transaction evidence, and prepared a simple income statement based on the principles of SAK EMKM. Cash examination also indicated that the physical cash balance was consistent with the recorded balance, although weaknesses remained in task segregation and document archiving. The findings demonstrate that practical accounting education and continuous mentoring can improve financial literacy, recording discipline, accountability, and decision-making capacity among micro-scale businesses. This intervention provides a replicable model for strengthening financial governance and supporting sustainable MSME development.